“The Athens of Volhinia” in Krzemieniec and his “Medal Cabinet” - Filipow , Krzysztof (Acta Archaeologica Lodziensia, 2023)
The Volhynian Gymnasium, later transformed into the Volhynian Lyceum, known as “The Athens of Volhinia”, was a Polish High-School in Krzemieniec in Volhynia. It was founded by Tadeusz Czacki, then inspector of educational establishments in the Volhynia, Kiev and Podolia governorates, with the participation of Hugo Kołłątaj. It existed during the years 1805-1831, and was reactivated in the years 1922-1939. It played a significant role in the development of the level of Polish culture in Volhynia. In Krzemieniec there was a “Medal Cabinet”, with a valuable numismatic collection based on part of the collection left after Stanisław August Poniatowski. Coins from ancient to contemporary periods were gathered there, and part of the gold medals of the “royal series”. The numismatic collection was intended for didactic use. For this purpose, printed “lectures” were prepared by Tadeusz Czacki. Franciszek Rudzki was particularly instrumental in developing the collection. The collection was moved to Vilnius after the fall of the November Rising. Later it was dispersed to other academic centres in Kiev and Kharkov.